Energy efficiency of a direct-injection internal combustion engine with high-pressure methanol steam reforming. (August 2015) - Poran, Arnon; Tartakovsky, Leonid
Abstract: This article discusses the concept of a direct-injection ICE (internal combustion engine) with thermo-chemical recuperation realized through SRM (steam reforming of methanol). It is shown that the energy required to compress the reformate gas prior to its injection into the cylinder is substantial and has to be accounted for. Results of the analysis prove that the method of reformate direct-injection is unviable when the reforming is carried-out under atmospheric pressure. To reduce the energy penalty resulted from the gas compression, it is suggested to implement a high-pressure reforming process. Effects of the injection timing and the injector's flow area on the ICE-SRM system's fuel conversion efficiency are studied. The significance of cooling the reforming products prior to their injection into the engine-cylinder is demonstrated. We show that a direct-injection ICE with high-pressure SRM is feasible and provides a potential for significant efficiency improvement. Development of injectors with greater flow area shall contribute to further efficiency improvements. Highlights: Energy needed to compress the reformate is substantial and has to be accounted for. Reformate direct-injection is unviable if reforming is done at atmospheric pressure. Direct-injection engine with high-pressure methanol reforming is feasible. Efficiency improvement by 12–14% compared with a gasoline-fed engine was shown.